A water soluble zinc phthalocyanine: physicochemical, electrochemical studies and electropolymerization. (20th September 2016) - L'Her, Maurice; Göktuğ, Özge; Durmuş, Mahmut; Ahsen, Vefa
Graphical abstract: Abstract: The physicochemical and electrochemical properties, including electropolymerization, of the water soluble 2, 9(10), 16(17), 23(24)-tetra-(2-mercapto-N-methylpyridinium)phthalocyaninato zinc(II), 1, have been studied in the present work. While this phthalocyanine is soluble in DMSO as the monomeric species, it exists as very stable dimers in aqueous solutions. These dimers break down into monomers upon addition of an anionic surfactant, sodium dodecylsulphate (SDS). The aqueous solutions of1 have been studied by rotating disc electrode, cyclic and square-wave voltammetries, and spectroelectrochemistry. Upon reduction, an electroactive film of the zinc(II) phthalocyanine is formed at the surface of the electrode, due to the reduction of the N-methylpyridinium groups which induces the formation of bispyridines and therefore the deposition of an insoluble polymer.